Safety and Efficacy of Early Tube Removal Following Percutaneous Transhepatic Gallbladder Drainage: an Observational Study. Issue 2 (April 2020) - Kamezaki, Hidehiro; Tsuyuguchi, Toshio; Shimura, Kenji; Sakamoto, Dai; Senoo, Junichi; Mizumoto, Hideaki; Kubota, Michio; Yoshida, Yu; Azemoto, Ryosaku; Sugiyama, Harutoshi; Kato, Naoya
Abstract : Background: There are currently no guidelines concerning the advisability and timing of tube removal following percutaneous transhepatic gallbladder drainage (PTGBD). The present study aimed to assess the feasibility and risks of early removal of the PTGBD tube under the scenario of subsiding inflammation, patent cystic and common bile ducts, and absence of intraperitoneal leakage. Methods: Patient background and outcomes were assessed retrospectively in 701 cases of acute cholecystitis treated with PTGBD. The median times until tube removal and tube dislodgement and the cumulative rates of tube dislodgement were calculated. Results: Tube removal was performed in 275 patients after a median time of 16 days (range: 6 to 213 d); biliary peritonitis was observed in 2 patients following tube removal. Tubes were removed in 8 and 35 patients within 7 and 10 days, respectively. Tube dislodgement was observed in 82 patients after a median time of 12 days (range: 1 to 125 d). Conclusion: The present study suggests that drainage tube removal is safe and effective when performed after a short drainage period of 7 to 10 days if the criteria for the removal of the drainage tube were met.